The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/1806-3713/e20170288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vaporized perfluorocarbon on oxidative stress during the cold ischemia phase of lung graft preservation

Abstract: Liquid perfluorocarbon (PFC) instillation has been studied experimentally as an adjuvant therapy in the preservation of lung grafts during cold ischemia. The objective of this study was to evaluate whether vaporized PFC is also protective of lung grafts at different cold ischemia times. We performed histological analysis of and measured oxidative stress in the lungs of animals that received only preservation solution with low-potassium dextran (LPD) or vaporized PFC together with LPD. We conclude that vaporize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…[11][12][13] For example, when an emulsified form of perfluorochemicals was administered directly into the blood vessels or the airway, relatively modest side effects were reported, including the elevation of blood pressure and injury to organs. 12,[17][18][19] The level of arterial oxygenation, if scaled for human application, is likely sufficient to alleviate patients with severe respiratory failure. -PFD potentially provides lifesaving oxygenation, while there is additional room for improving gas exchange efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] For example, when an emulsified form of perfluorochemicals was administered directly into the blood vessels or the airway, relatively modest side effects were reported, including the elevation of blood pressure and injury to organs. 12,[17][18][19] The level of arterial oxygenation, if scaled for human application, is likely sufficient to alleviate patients with severe respiratory failure. -PFD potentially provides lifesaving oxygenation, while there is additional room for improving gas exchange efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, PFC is easily distributed throughout the lungs in a more uniform manner during the vaporization process and will not cause lung ventilation difficulties caused by infusion of liquid PFC. In a cold ischemia rat model, vaporized PFC + LPD preserved lungs exhibited higher superoxide dismutase (SOD) concentrations than LPD alone, suggesting that use of vaporized PFC reduces free radical production, which in turn protects lung grafts from oxidative stress damage …”
Section: Application Of Oxygen Carriersmentioning
confidence: 99%
“…In a cold ischemia rat model, vaporized PFC + LPD preserved lungs exhibited higher superoxide dismutase (SOD) concentrations than LPD alone, suggesting that use of vaporized PFC reduces free radical production, which in turn protects lung grafts from oxidative stress damage. 103 3.2.3. Application of PFC Oxygen Carriers in Tumor Therapy.…”
Section: Application Of Pfc Oxygen Carriers In Organmentioning
confidence: 99%
“…In previous studies, PFT was mentioned as potential preventive strategy for ischemia/reperfusion injuries for example in lung graft preservation (14). Also, it is suggested that PFT could decrease production of inflammatory markers and stress oxidative markers, decrease lung oedema and hydroxyproline level, as well as attenuate histopathological changes and fibrosis (15).…”
Section: Introductionmentioning
confidence: 99%